Factors affecting instructors' adoption of learning management systems: a theoretical framework - Abdallah, Nahel A. O.; Ahlan, Abdul Rahman; Abdullah, Odeh Abed (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Higher educational institutions have made a substantial investment in the adoption of Learning Management Systems to enhance their learning and teaching activities, however, these systems are not used by the faculty members with their fullest capabilities. This research mainly aims to verify the key factors that affect learning management system (LMS) adoption by instructors in Palestinian universities and to develop an integrated model of instructor adoption of e-learning management systems by incorporating existing literature and multiple empirically verified multiple theories. A theoretical framework isproposed based on Delone and McLean information system success model, Technology Acceptance model, and Self-Determination Theory Model. This framework gives a comprehensive look at the significant factors that control and affect the instructors' adoption to the learning management system. These key factors are related to the instructor, organization, society, belief, and technology.